Effect of acidity and texture of micro-, mesoporous and hybrid micromesoporous materials on the synthesis of paramenthanic diol exhibiting anti-Parkinson activity. (3rd July 2015) - Torozova, A.; Mäki-Arvela, P.; Shcherban, N. D.; Kumar, N.; Aho, A.; Stekrova, M.; Maduna Valkaj, K.; Sinitsyna, P.; Filonenko, S. M.; Yaremov, P. S.; Ilyin, V. G.; Volcho, K. P.; et al.
Abstract: Microporous, mesoporous and new hybrid materials were studied in verbenol oxide isomerization for the synthesis of biologically active substance with anti-Parkinson activity. H-Si-MCM-41, H-Al-MCM-41, H-Al-MCM-48, H-Beta-25 and H-Beta-300 were compared with hybrid materials. The latter with a zeolite-like micro-mesoporous structure were characterized and evaluated for their catalytic activity for the first time. The approach of dual templating for synthesis of new materials was applied in this work to combine properties of Beta-zeolites and mesoporous cellular foams. The selectivity to the target product was the highest over microporous mild acidic H-Beta-300 and hybrid ZF-100, with also mild acidity and even absence of strong acid sites. Selectivity at 97% and 99% of conversion was 61% and 59% for H-Beta-300 and hybrid ZF-100, respectively. Abstract :